2004
DOI: 10.1021/bi036208p
|View full text |Cite
|
Sign up to set email alerts
|

Two Apolipoprotein E Mimetic Peptides, ApoE(130−149) and ApoE(141−155)2, Bind to LRP1

Abstract: LRP1 is a cell surface receptor responsible for clearing some 30 known ligands. We have previously shown that each of the three complete LDL receptor-homology domains of the LRP1 extracellular domain (sLRPs) binds apoE-enriched beta-VLDL particles. Here we show that two peptides from the N-terminal receptor binding domain of apoE, which are known to elicit a number of different cellular responses, bind to LRP1. Solution binding assays show that the two peptides, apoE(130-149) and apoE(141-155)(2), interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
74
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(80 citation statements)
references
References 34 publications
6
74
0
Order By: Relevance
“…These immune‐modulatory effects on microglial by CN‐105 are consistent with apoE15, 16, 17, 54 and other apoE‐mimetic peptides 17, 34. LRP1, a cell surface receptor, has been shown to bind apoE55 and other apoE‐mimetic peptides 29, 56. The function of this interaction between apoE and LRP1, has been associated with suppression of neuroinflammation 57.…”
Section: Discussionmentioning
confidence: 52%
“…These immune‐modulatory effects on microglial by CN‐105 are consistent with apoE15, 16, 17, 54 and other apoE‐mimetic peptides 17, 34. LRP1, a cell surface receptor, has been shown to bind apoE55 and other apoE‐mimetic peptides 29, 56. The function of this interaction between apoE and LRP1, has been associated with suppression of neuroinflammation 57.…”
Section: Discussionmentioning
confidence: 52%
“…It has been shown previously that heparin can interact with a variety of functional modulators of the NMDAR, and, consequently, abrogate their effects in this system (Charriaut-Marlangue et al, 1991;Pittaluga et al, 2000) Since we show that heparin, alone, does not effect ion currents through the NMDAR in our system, we conclude that heparin exerts its effects via interaction with apoE [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149], an interaction that is known to occur (Croy et al, 2004;Weisgraber et al, 1986) 9and this study). Heparin also interacts with ligands of LRP that contain heparin binding domains, and inhibits the interaction of these ligands with LRP.…”
Section: Discussionmentioning
confidence: 99%
“…Separate studies (data not shown) have demonstrated that heparin did not affect whole cell currents in NR1b/2A-transfected HEK293 cells, when present alone. We considered that the effects of heparin in the presence of apoE [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] are due to its interaction with apoE [133][134][135][136][137][138][139][140][141][142][143][144][145][146][147][148][149] (Croy et al, 2004;Weisgraber et al, 1986). This was confirmed by SPR, as shown in the inset of Fig.…”
Section: The Lrp Ligands Rap and α 2 M* Alter The Effects Of Apoe[1mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to binding to the LDLR, the stringency for binding of apoE to the LRP or HSPG appears to be less severe. Lipid association of apoE is not required for binding to the LRP (31) or HSPG (22,32), although the same apoE domain spanning residues 136 -150 is involved in the binding (21,33). ApoE2 that is highly defective in LDLR binding activity (Ͻ2% of normal apoE3 activity) has significant binding activity to LRP (40 -50% of apoE3) (23) and HSPG (50 -90% of apoE3) (6).…”
mentioning
confidence: 99%